(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
The mixed compound NaH2(PO4)0.48(AsO4)0.52.H2O, which has been examined by Raman spectroscopy, XRD powder and dielectric, exhibits solid–solid phase transitions and one reversible solid–liquid phase transition. Besides, the investigation of dehydration behavior of sodium dihydrogenate phosphate-arsenate monohydrate was undertaken in a temperature range from 253 K to 333 K. The onset temperature of dehydration was determined from changes in ionic conductivity and X-ray powder on heating. It was confirmed by the Raman study not only in the disappearance of the vibrations assigned to the PO4, AsO4 but also in the appearance of the new vibrations attributed to the (PO3), which constitutes the P-O-P chain, giving a polymer with the formula: NaH2(P2O7)x(As2O7)(1-x). The important variation was observed in all studies at 313 K, which could correspond to the transformation of the NDAP compounds of a solid crystal into a liquid form.